The Liability of Leading: Battling Aspiration and Survival Goals in the Jeopardy! Tournament of Champions - Boyle, Elizabeth; Shapira, Zur (Organization Science, 2012)
We extend the variable risk preferences model of decision making to a competitive context in order to develop theory about how competition affects both focus of attention and risk taking. We hypothesize and find support for leader–follower differences in the channeling of attention to an aspiration or survival point. Our results indicate that leaders focus on their aspiration point, whereas followers' focus of attention shifts between their aspiration and survival points. By identifying and elaborating on the different cognitive loads and social expectations related to the positions of leader and follower, we show that leaders are prone to take excessive risks to maintain their leadership position. We refer to this phenomenon as the liability of leading. Our study context is a naturally occurring experiment in strategic decision making, the Jeopardy! Tournament of Champions.